Net-charge fluctuations in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Constantin, Paul; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; et al. (Physical review letters, 2013)
We report the first measurement of the net-charge fluctuations in Pb-Pb collisions at √sNN=2.76 TeV, measured with the ALICE detector at the CERN Large Hadron Collider. The dynamical fluctuations per unit entropy are observed to decrease when going from peripheral to central collisions. An additional reduction in the amount of fluctuations is seen in comparison to the results from lower energies. We examine the dependence of fluctuations on the pseudorapidity interval, which may account for the dilution of fluctuations during the evolution of the system. We find that the fluctuations at the LHC are smaller compared to the measurements at the BNL Relativistic Heavy Ion Collider, and as such, closer to what has been theoretically predicted for the formation of a quark-gluon plasma.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Constantin, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, K. Koch, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, S. Radomski, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J.H. Stiller, J. Ulrich, S. Vallero, Y. Wang, B. Windelband, A. Zimmermann und weitere 965
Gesehen am 30.04.2021